Identification of a Novel Non-desmoglein Autoantigen in Pemphigus Vulgaris - Di Lullo, Giulia; Calabresi, Valentina; Mariotti, Feliciana; Zambruno, Giovanna; Lanzavecchia, Antonio; Di Zenzo, Giovanni (Frontiers in Immunology, 2019)
Pemphigus vulgaris (PV) is an autoimmune bullous disease of the skin and mucous membranes characterized by the presence of circulating and tissue-bound autoantibodies against keratinocyte cell surface antigens, specifically desmoglein (Dsg) 1 and 3. The pathogenic role of anti-Dsg antibodies is well-established, while the mechanism of blister formation is only partly defined. We have applied a previously developed method for the efficient immortalization of IgG+ memory B cells to identify novel target antigens in PV. A human monoclonal antibody reactive with a hitherto unreported non-Dsg antigen was isolated. Immunoprecipitation and immunoblotting studies with keratinocyte extracts indicated α-catenin as the putative antigen, then confirmed by immunoblotting on the recombinant protein. Four of ten PV sera reacted with recombinant α-catenin. Although the isolated human monoclonal antibody was per se unable to dissociate keratinocyte monolayers and also to synergize with a pathogenic antibody in vitro, further studies are warranted to assess its possible in vivo contribution in the multifactorial pathogenesis and heterogeneous manifestations of PV disease.